The effect of prayer on god's attitude toward mankind - James Joseph Heckman (Institute for the Study of Labor (IZA), 2008)
This paper uses data available from the National Opinion Research Center's (NORC) survey on religious attitudes and powerful statistical methods to evaluate the effect of prayer on the attitude of God toward human beings.
urn:nbn:de:101:1-20080820219
Keywords: Z12; 330; Kernel estimator; unobserved variables; Religion; Meinung; Schätztheorie; Theorie; USA